Determination of some trace metals in water of Shatt Al-Arab River during 2007-2008 - M. Nasir, Ali; B. Abdullah, Shaker; T. L. Al-Yaseri, Sami (University of Thi-Qar Journal of Science, 2011)
The present study is an attempt for assessment the aquatic ecosystem of Shatt Al- Arab Riverby measuring the trace metals ( Cd , Co , Ni , Pb , Cu and Fe ) in water collected in fourlocations (Qurmat-Ali , Al-Muftiya , Al-Seba and Rass Al-Besha) which represent differentlevels and sources of human impact., the results showed that the highest concentration of the trace metals in the Rass Al-Besha location ( 14.48 , 84.24 , 38.74 , 41.09 , 10.55 , 145.49 ) μg ⁄ lfor trace metals (Cd , Co , Ni , Pb , Cu and Fe) respectively , the highest concentration of thetrace metals is Cadmium in all locations , Cobalt was the highest in two locations ( Rass Al-Besha and Al- Seba ) comparing with the concentrated standard allowed by the system ofmaintenance of River pollution form No. 25 of 1967 (Service Specifications Iraqi andstandards) , and levels in the international determinate of draft drainage from world healthorganization WHO, 1993 and Japan specification EQS ,2001. While the lowest concentration (4.25 , 39.76 , 11.80 ) μg ⁄ l for trace metals (Cd , Co , Ni ) respectively in the Qurmat-Alilocation , ( 21.60 , 64.44 ) μg ⁄ l for Pb and Fe respectively Al-Muftiya location , 5.25 μg ⁄ lfor Cu in the Al- Seba location .